HUBUNGAN POSISI DAN LAMA DUDUK SELAMA PERKULIAHAN TERHADAP KELUHAN LOW BACK PAIN MEKANIK Tinjauan pada mahasiswa program studi kedokteran program sarjana FK ULM angkatan 2019-2021 - Somantri, Nizam Al Fikri; Hayati, Azka; Asnawati, Asnawati; Noor, Zairin; Fakhrurrazy, Fakhrurrazy (Homeostasis, 2023)
Mechanical low back pain is lower back pain in normal anatomical structures that are overused or secondary to mechanical trauma that puts stress on muscles, tendons, and ligaments. This study aims to determine the association between position and long sitting during lectures to complaints mechanical LBP in PSKPS FK ULM students class of 2019-2021. This study used a descriptive analytic research design with a cross sectional approach to 45 students who met the criteria. The results of this study found that the sitting position was not ergonomic (64.4%), the sitting position was ergonomic (35.6%), sitting ≤4 hours/day (44.4%), and sitting >4 hours/day (55.6%). Analysis using the chi square test, the association between sitting position during lectures to complaints mechanical LBP was obtained p value=0.005; and the association between long sitting during lectures to complaints mechanical LBP obtained p value=0.027. The conclusion of this study is that there is a significant association between position and long sitting during lectures to complaints mechanical LBP in PSKPS FK ULM students class of 2019-2021.